NBER Digest - National Bureau of Economic Research (Cambridge, MA National Bureau of Economic Research (NBER))
The Digest is a publication that summarizes at least four recent and newsworthy NBER Working Papers. Professional journalists write these summaries for a non-technical audience.
The Digest is a monthly publication issues (1995-2004) are not registered in the Cardex Available in electronic form only, last hard copy received end of 2013
Keywords: Economics; ECONOMIC DEVELOPMENT; RESEARCH; PERIODICALS